Susceptibility of stored chickpeas to bruchid infestation as influenced by physico-chemical traits of the grains. (May 2020) - Swamy, SVS.Gopala; Raja, D.Sandeep; Wesley, B.John
Abstract: A total of nine promising varieties including five desi type and four kabuli type of chickpeas were screened against pulse bruchid under free-choice conditions at Post Harvest Technology Centre, Bapatla. The chickpeas were studied for their physical characters and biochemical constituents, and the extent of influence on insect preference and development was established through correlation and regression analyses. The varieties; NBeG 511, JAKI 9218 and JG 11 which had less numbers of eggs and adult emergence, with low per cent grain damage were found to be desi type and possessed less test weight with higher seed coat thickness. Similarly the varieties; NBeG 458, NBeG 471 and KAK 2 which recorded higher oviposition, adult emergence and grain damage were found to have thin seed coat and larger seed size. Thus, test weight of the grains showed significant positive correlation to adult emergence and grain damage while seed coat thickness showed the negative correlation. Chickpea grains with higher sugar and lower phenol contents were found to be more susceptible to bruchids. Though there were significant differences in the contents of biochemical constituents of chickpeas of these cultivated varieties, they could not exert significant influence on bruchid development. Highlights: The desi type chickpea varieties which possessed less test weight with thicker seed coat recorded less adult emergence and grain damage. The chickpea varieties which recorded higher oviposition, adult emergence and grain damage had thin seed coat and larger seed size. Adult emergence and grain damage had significant positive correlation with test weight of the grain. Chickpea grains with higher sugar and lower phenol contents were more susceptible to pulse bruchid.